DINAMIKA INTERAKSI GEO-FINANCE DALAM MENGANTISIPASI KRISIS GREEN FINANCE DI INDONESIA - Edwin Basmar; Hasan Hasan (Journal of Accounting and Finance, 2026)
The high volatility of global economic pressures (geo-finance) has caused national financial turbulence to experience severe stress. This study aims to identify the effects of external pressures on the potential for a green finance crisis in Indonesia. The research also reveals symptoms of financial movements in the banking sector that trigger a green finance crisis. Financial pressure disclosure is measured based on Bank Indonesia financial reports from 2015–2025 as indicators of financial movement, calculated through the Ed Waves Index development model using EViews 9 software. The results show that the potential for a green finance crisis in Indonesia is highly significant, driven by geo-finance (external) pressures that cause shifts within the banking system (internal). Furthermore, shifts in financial pressure increase financial sensitivity, threatening the macroeconomic elements movement in achieving financial stability and economic growth. The findings imply that geo-finance pressure is a major triggering factor that strongly intensifies the green finance crisis in Indonesia as a developing country.